Analisa Efektivitas Model GR4j Guna Pengalihragaman Hujan Menjadi Debit (Studi Kasus : DAS Siak Hulu) - Ega Riana Tovani; Manyuk Fauzi; Imam Suprayogi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
On this studyto review the rainfall-runoff modeling of GR4J (Ge'nie Rurala`4parame`tres Journalier) on Watershed (DAS) Siak hulu. In this study using two methods:by modeling GR4J and length of the data elaboration method for calibration and verification. This GR4J models using input data including daily data of rainfall at the Petapahan baru stationand daily data of evapotranspiration potential is the result of a program CropWat within input data is climatological data at Pasar Kampar stations, modeling results is tested using daily data of discharge observations on the Pantai Cermin station. This modeling to optimize four free parameters such as Maximum Capacity Production Store(X1), Coefficient Changes in Ground water(X2), Maximum Capacity Routing Store(X3), and Peak Time Ordinate unit hydrograph (X4). In the second method, performed of calibration in certainly year and verification in thereafther. As a determinant of the model’s success is use dequation NashSutcliffe Coefficient (R2) and the correlation coefficien tmethod(R) to calculate the deviation occurs. Keywords:GR4J,Calibration, verification.